Prevalence and density of Elaphostrongylus rangiferi larvae in faecal samples of semi-domestic reindeer (Rangifer tarandus tarandus) in Norway 2013-16 - Terje Domaas Josefsen; Torill Mørk; Ingebjørg Helena Nymo; Javier Sanchez Romano; Morten Tryland (Acta Veterinaria Scandinavica)
Abstract Background The reindeer brainworm, Elaphostrongylus rangiferi, is a protostrongylid parasite of reindeer that has caused severe disease outbreaks in reindeer husbandry. E. rangiferi is considered ubiquitous in Norway, though most published prevalence studies are from Finnmark county only. In the present study, faecal samples were collected over three winter seasons (2013–2016) from eight herds of semi-domesticated Eurasian tundra reindeer (Rangifer tarandus tarandus) distributed all over the reindeer herding area in Norway. Baermann’s technique was used to identify E. rangiferi larvae. The density of larvae was measured by counting and calculating number of larvae per gram faeces (LPG) in positive samples. Results E. rangiferi larvae were found in 109 of 355 faecal samples (31%). All herds had positive samples at all sampling sessions. Prevalence in adults (> 1.5 years, n = 176) was 43% with significant difference between herds, varying from 25 to 78%. Prevalence in calves (< 1 year, n = 179) was 18%, and varied with sample month, being 10% in Oct-Jan (n = 153) and 69% in Mar-May (n = 26). Prevalence did not show statistically significant difference between males and females. LPG showed a highly skewed distribution, total median LPG being 38, range 2-700. Calves in Mar-May had significantly (P = 0.01) higher number of LPG (median 104) than calves in Oct-Jan (median 14) and adults (median 32). LPG did not differ significantly between males and females nor between herds, but there was a significant moderate positive correlation between herd prevalence and LPG (Spearman rho = 0.35, P < 0.01). Samples from individually marked adult reindeer with known age (n = 81) showed no significant difference in prevalence between young (2–5 years) and old (6–15 years) reindeer. LPG tended to be slightly reduced with age, but the reduction was not statistically significant (P = 0.07). Systematic yearly treatment with ivermectin was done in four herds, but any effect on E. rangiferi prevalence was not clear. Conclusions This study confirms that E. rangiferi was ubiquitously present in all parts of the reindeer herding area in Norway during the study period. Differences in prevalence between herds were significant, and LPG in herds increased with increasing herd prevalence.